Impact of lympho-vascular space invasion on tumor characteristics and survival outcome of women with low-grade serous ovarian carcinoma - Matsuo,K; Wong,K-K; Fotopoulou,C; Blake,EA; Robertson,SE; Pejovic,T; Frimer,M; Pardeshi,V; Hu,W; Choi,J-S; Sun,CC; Richmond,AM; et al. (Journal of Surgical Oncology, 2017)
BACKGROUND AND OBJECTIVES: To examine association of lympho-vascular space invasion (LVSI) with clinico-pathological factors and to evaluate survival of women with low-grade serous ovarian carcinoma containing areas of LVSI. METHODS: This is a multicenter retrospective study examining consecutive cases of surgically treated stage I-IV low-grade serous ovarian carcinoma (n = 178). Archived histopathology slides for the ovarian tumors were reviewed, and LVSI was scored as present or absent. LVSI status was correlated to clinico-pathological findings and survival outcome. RESULTS: LVSI was seen in 79 cases (44.4%, 95% confidence interval [CI] 37.1-51.7). LVSI was associated with increased risk of omental metastasis (87.0% vs 64.9%, odds ratio [OR] 3.62, P = 0.001), high pelvic lymph node ratio (median 12.9% vs 0%, P = 0.012), and malignant ascites (49.3% vs 32.6%, OR 2.01, P = 0.035). On multivariable analysis, controlling for age, stage, and cytoreductive status, presence of LVSI in the ovarian tumor remained an independent predictor for decreased progression-free survival (5-year rates 21.0% vs 35.7%, adjusted-hazard ratio 1.57, 95%CI 1.06-2.34, P = 0.026). LVSI was significantly associated with increased risk of recurrence in lymph nodes (OR 2.62, 95%CI 1.08-6.35, P = 0.047). CONCLUSION: LVSI in the ovarian tumor is associated with adverse clinico-pathological characteristics and decreased progression-free survival in women with low-grade serous ovarian carcinoma.